Multiculturalism under Threat and Strategies in Constructing Inclusive Spaces in Europe and Southeast Asia Regions - Regus, Maksimus (Global Focus, 2023)
Multiculturalism is among the best solutions to social groups' clashes, tensions, and conflicts. It provides an open, fair, and equal political and social policy to all elements in one society. However, multiculturalism strengthens radicalism and terrorism when the attention and respect for social identity are unequal. This article examines multiculturalism's situation, trends, and challenges in the European and Southeast Asian regions. Additionally, the paper elaborates on the challenges of building inclusive spaces in multicultural societies. Data were analyzed using a systematic-critical qualitative review method. Information was sourced from previous studies, reports from international websites, news, and analyses on the condition of multiculturalism in these two regions.